Concept, motives and channels of digital shadow economy: consumers’ attitude - Gasparėnienė, Ligita; Remeikienė, Rita; Schneider, Friedrich Georg (Journal of Business Economics and Management, 2017)
The purpose of this article is to define the concept of digital shadow economy and identify its determinants and channels from consumers’ position. In order to fulfil the defined purpose, the method of snowball sampling was employed. The results of the research revealed that consumers interpret digital shadow economy as an illegal operation in the Internet space, which generates illegal money flows for commodity/service providers or purchasers, and deprives legal traders/service providers from the revenue that could be officially accounted, calculated and declared. E-shops, social networks and websites are the channels, most commonly engaged for acquisition of goods/services in digital space; the categories of goods/services acquired by these channels include clothing and footwear, trips and entertainment, cosmetics and perfume. Purification of the concept of digital shadow economy from consumers’ position allowed to define the concept of digital shadow economy, which is a significant contribution to the evolution of the theory of digital shadow economy, and can enable to develop an instrument for measuring the scopes of digital shadow economy in further research.